Reduktion der Tinnituslautstärke: Pilotstudie zur Abschwächung von tonalem Tinnitus mit schwellennahem, individuell spektral optimiertem Rauschen - Schilling, Anne; Krauß, Patrick; Hannemann, R.; Schulze, Holger; Tziridis, Konstantin (HNO, 2020)
Background: Around 15% of the general population is affected by tinnitus, but no real cure exists despite intensive research. Based on our recent causal model for tinnitus development, we here test a new treatment aimed at counteracting the perception. This treatment is based on the stochastic resonance phenomenon at specific auditory system synapses that is induced by externally presented near-threshold noise. Objective: This pilot study will investigate whether individually spectrally adapted noise can successfully reduce chronic tonal/narrow-band tinnitus during stimulation. Materials and methods: Hearing loss (HL) as well as tinnitus pitch (TP) and loudness (TL) were audiometrically measured in 22 adults (46.6±16.3 years; 4 women) with tinnitus. Based on these measurements, up to eight different noise stimuli with five intensities (−20 to +20 dB SL) were generated. These were presented for 40 s each via audiologic headphones in a soundproof chamber. After each presentation, the change in TL was rated on a five-level scale (−2 to +2). Results: We found patients (n = 6) without any improvement in their TL perception as well as patients with improvement (n = 16), where stimulation around the TP was most effective. The groups differed in post-hoc analysis of their audiograms: the effectiveness of our new therapeutic strategy obviously depends on the individual HL, and was most effective in normal-hearing tinnitus patients and those with mild HL. Conclusion: Subjective TL could be reduced in 16 out of 22 patients during stimulation. For a possible success of a future therapy, the HL seems to be of relevance.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Hearing loss; Individualized therapy; Pure tone audiometry; Stochastic resonance; Tinnitus questionnaires